Massive neutrinos in physics and astrophysics - Mohapatra, R. N (World Scientific, 2004)
The recent groundbreaking discovery of nonzero neutrino masses and oscillations has put the spotlight on massive neutrinos as one of the key windows on physics beyond the standard model as well as into the early universe. This third edition of the invaluable book Massive Neutrinos in Physics and Astrophysics is an introduction to the various issues related to the theory and phenomenology of massive neutrinos for the nonexpert, providing at the same time a complete and up-to-date discussion on the latest results in the field for the active researcher.